VISION STATEMENTS: ELEMENTARY OF DECISION-MAKING - Amy Austen (PUPIL: International Journal of Teaching, Education and Learning, 2026)
Vision statements are intended to serve as a formalised tool for communicating organisational vision (Kantabutra, 2023). Although the content of and fidelity to vision statements have been found to influence the cohesion of school culture and leadership (Baildon & Arabi, 2023), their development and enactment remain poorly understood (Bialik & Merhav, 2020). To address this, the perspectives of principals of independently governed Protestant schools on the development and enactment of vision statements were examined. This study used an interpretive qualitative design, conducted 11 semi-structured interviews, and analysed them using Grounded Theory methods. A key finding was that principals in this study largely based decision-making on the vision statements in two areas: strategic planning and operational decisions. The principals detailed that vision statements serve as the foundation or umbrella for strategic planning, in that all other elements of the strategic plan can be tied to the vision statement. They also explained that they assessed significant operational decisions for the school against their school’s vision statement’s intent, acted on decisions they deemed supportive of the vision statement, and made changes to those that did not. By incorporating the vision statement into decision-making, principals saw themselves as a mechanism for implementing it, thereby contributing to the vision statement’s sense of fidelity.